1985
DOI: 10.1093/oxfordjournals.aje.a114086
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and Validity of a Semiquantitative Food Frequency Questionnaire

Abstract: The aim of this study was to evaluate the reproducibility and validity of a 61-item semiquantitative food frequency questionnaire used in a large prospective study among women. This form was administered twice to 173 participants at an interval of approximately one year (1980-1981), and four one-week diet records for each subject were collected during that period. Intraclass correlation coefficients for nutrient intakes estimated by the one-week diet records (range = 0.41 for total vitamin A without supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

87
2,648
5
43

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 3,800 publications
(2,817 citation statements)
references
References 0 publications
87
2,648
5
43
Order By: Relevance
“…Usual dietary intake was determined at baseline using a semiquantitative 66‐item food‐frequency questionnaire administered by trained interviewers to improve accuracy and completeness 23, 24. Frequency and portion size of each food item were multiplied by nutritional content from US Department of Agriculture sources to estimate intake of micro‐ and macronutrients.…”
Section: Methodsmentioning
confidence: 99%
“…Usual dietary intake was determined at baseline using a semiquantitative 66‐item food‐frequency questionnaire administered by trained interviewers to improve accuracy and completeness 23, 24. Frequency and portion size of each food item were multiplied by nutritional content from US Department of Agriculture sources to estimate intake of micro‐ and macronutrients.…”
Section: Methodsmentioning
confidence: 99%
“…Diet was assessed with a validated food frequency questionnaire that asked how often, on average, a participant had consumed a particular amount of a specific type of food during the previous year 12. The intake of nutrients was computed by multiplying the frequency of consumption of each unit of food by its nutrient content, and consumption of alcoholic drinks was also considered.…”
Section: Methodsmentioning
confidence: 99%
“…SSHIP-I participants completed the Willett Food Frequency Questionnaire (FFQ), 29 a widely used paper-and-pencil, semi-quantitative measure that asks participants to estimate how often, on average, they have consumed a variety of foods over the past year (serving sizes provided). The questionnaire includes nine possible responses ranging from "never" to "6ϩ times per day."…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire includes nine possible responses ranging from "never" to "6ϩ times per day." Willett et al 29,30 reported correlations between the FFQ and 1-year diet records of 0.44 -0.76, and 1-year test-retest reliability coefficients of 0.54 -0.70. The Willett FFQ composite scores used in this study were total fat (gm), saturated fat (gm), carbohydrates (gm), protein (gm), total calories (kcal), cholesterol (mg), sodium (mg), and dietary fiber (gm).…”
Section: Methodsmentioning
confidence: 99%